Management Curriculum Analysis of Education Program at San Rafael Correctional Institution, in Alajuela, Costa Rica - Murillo Brenes, Jeffrey (2012)
This article is a research conducted at San Rafael Correctional Institution in Alajuela, Costa Rica. The study applied research based on a qualitative approach through the following objectives: identify curricular design adjustments to educational programs in this center. Besides this, to recognize pedagogical components that have correctional institutions to implement educational programs, determining the curricular pertinence to population needs, and identify the curricula assessment system used for management of this institution. The findings allowed obtaining basic knowledge to restructure not only educational programs, but procedures required to teach learners inmates in prisons in Costa Rica.